Model of reed valve dynamics in unsteady flow, solution algorithm, and validation on a single-cycle rig - Enikeev, R. D.; Chernousov, A. A. (Vestnik Samarskogo universiteta. Aèrokosmičeskaâ tehnika, tehnologii i mašinostroenie (Online), 2024)
The results of studying an application model of unsteady flow through the reed valve assembly of a two-stroke piston engine are presented. The main goal was to develop and validate a model based on the check valve calculation scheme in the ALLBEA software package. The principles of modeling the valve motion dynamics in conjunction with a one-dimensional model of gas dynamics, as well as the algorithmic presentation of calculations for their implementation in the package, are briefly discussed. An approach to valve model identification and the proposed method for adjusting the model coefficients are considered. For the identification and validation of the model the data obtained from a single-cycle experimental setup were used, in which flow through the reed valve with finite amplitude waves in the pipeline was organized. The conducted research contributes to the analysis and optimization of processes in pipelines, pumps, and engines, promotes the development of applied models, software tools, and calculation methods in the specified areas.